Tillandsia ramon-lopezii: a new species from Venezuela, similar to T. brachycaulos (Bromeliaceae) - Ramírez-Morillo, Ivón; Fernández-Concha, Germán Carnevali; Pinzón, Juan P.; Tamayo Cen, Iván (Phytotaxa, 2024)
A species of Tillandsia, Tillandsia ramon-lopezii, from northern Venezuela, is proposed as new. The new taxon belongs in a group of species that are morphologically similar to T. brachycaulos but whose relationships require clarification. A full description, relevant iconography, including scanning electron microscope (SEM) images of peltate foliar and floral bract scales, and a discussion of affinities are provided. The conservation status of the new species was assessed using the IUCN Red List Criteria as LC.